Penerapan Media Pembelajaran Animasi Menggunakan Animiz untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Kelas X SMAN 1 Ciawigebang - Distira, Dikri Adiya; Mahpudin, Asep (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to utilize animation learning media developed using Animiz software, to improve students' academic achievement in Indonesian Language subjects in class X of SMAN 1 Ciawigebang. The approach used in this study is quantitative with experimental methods, especially using Quasi Experiment design. The research design applied is a nonequivalent control group design. This study adopts a Quasi Experiment design, in which two groups of classes are the subjects of the research: X-G class as the experimental class and X-J class as the control class. The experimental class uses Animiz media, while the control class follows conventional learning methods. Student learning outcome data is collected through pretest and posttest which involves observation and tests. The data analysis technique uses the t-test. The results of the study show that the application of Animiz Animation Maker animation learning media has succeeded in increasing students' understanding of poetry material in Indonesian Language subjects in class X of SMAN 1 Ciawigebang